The State's Transcendental Approach to Fulfilling The Indonesian Halal Industry Model of Policy - Uum Ummul Muhimah; Fatkhul Muin (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
The need for a halal industry encourages efforts to create a policy model that can guarantee the public to obtain halal products. Efforts to protect the public against halal products must of course start from government policies to formulate legal norms into laws and institutions that handle them. Article 10 of Law No. Law of the Republic of Indonesia Number 6 of 2023 concerning the Determination of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation into Law, that the Cooperation of BPJPH with the Central, Provincial, Regency/City Indonesian Ulema Council, or the Aceh Ulema Consultative Assembly as referred to in Article 7 paragraph (1) letter c is carried out in terms of determining the halal of Products. The halal industry that is developing in accordance with the needs of the Indonesian people who are predominantly Muslim, must be carried out massively, so that the rights of the community to halal products from the halal industry in the form of food, drinks and other products can be fulfilled by the state. This study focuses on the dynamics of state policy towards the halal industry in Indonesia with a state foundation based on religion in accordance with the provisions of the 1945 Constitution of the Republic of Indonesia, using a qualitative method with a legal approach as an analysis in this study.